Privatisation. - Ho, Bee Tat. (2009)
This report explores the various approaches and techniques of privatisation employed in Singapore and other countries. It attempts to understand the rationale and objectives behind each process of privatisation. Case study analysis is carried out on Malaysia, South Korea, United Kingdom and Singapore.